Assessing glacier changes in the Nanga Parbat region using a multitemporal photographic dataset - Nüsser, Marcus; Schmidt, Susanne (Data in Brief, 2021)
This article presents a multitemporal photographic dataset from the Rupal Valley, south of Nanga Parbat in the north-western Himalaya. The historical metric photographs were taken in 1934, 1958 and 1987 during scientific expeditions focussing on topographical mapping and glacier dynamics of the mountain massif. All photographs showing glacier aspects have been collected from archives and repeated from the same viewpoints during several surveys between 1992 and 2010. This dataset allows for a detailed visual assessment of glacier fluctuations, changes in snout positions, ice volumes, and debris cover over almost eighty years. It offers insights for a better understanding of glacier changes in this prominent Himalayan mountain region. The dataset supports a recently published article (Nüsser and Schmidt, 2021) with original archival material.
Gesehen am 18.06.2021